PENINGKATAN KEMAMPUAN MEMBACA INTENSIF DENGAN STRATEGI DRTA SISWA SEKOLAH DASAR - Misvaindra, Dolandari; F, Farida; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe an increase in intensive reading skills with the DRTA strategy of class III students at SD Negeri 46 Kuranji, Padang City. This type of research is classroom action research, with a qualitative and quantitative approach. The subjects of this study were class III students and teachers of SD Negeri 46 Kuranji, Padang City. The results of the research in each cycle showed an increase. The implementation of the teacher aspect of the first cycle was 67.18% (C), the second cycle was 87.5% (B). The implementation of aspects of the first cycle students was 60.93% (C), the second cycle was 90.62% (SB). The students' completeness results in cycle I 69.9 (C), with Prabaca 60.6, when reading 75.0 and post-reading 74.2. While the second cycle 82.5 (B) with Prabaca 78.0, when reading 84.3 and post-reading 85.1. It can be concluded that the DRTA Strategy can improve the intensive reading ability of grade III SDN 46 Kuranji students. Keywords: DRTA strategy, intensive reading ability.